A High-Sensitivity Graphene Metasurface and Four-Frequency Switch Application Based on Plasmon-Induced Transparency Effects - Aijun Zhu; Mengyi Zhang; Weigang Hou; Lei Cheng; Cong Hu; Chuanpei Xu (Photonics)
In this paper, we propose the use of a monolayer graphene metasurface to achieve various excellent functions, such as sensing, slow light, and optical switching through the phenomenon of plasmon-induced transparency (PIT). The designed structure of the metasurface consists of a diamond-shaped cross and a pentagon graphene resonator. We conducted an analysis of the electric field distribution and utilized Lorentz resonance theory to study the PIT window that is generated by the coupling of bright-bright modes. Additionally, by adjusting the Fermi level of graphene, we were able to achieve tunable dual frequency switching modulators. Furthermore, the metasurface also demonstrates exceptional sensing performance, with sensitivity and figure of merit (FOM) reaching values of 3.70 THz/RIU (refractive index unit) and 22.40 RIU-1, respectively. As a result, our numerical findings hold significant guiding significance for the design of outstanding terahertz sensors and photonic devices.